African Women in Neurosurgery An Exploration of Historical Perspectives, Current Realities, and Future Prospects - Boi-Dsane, N.A.A.; Venkatesh, P.; Tenkorang, P.; Omoba, O.; Limann, B.; Opara, A.; et al. (Women in Neurosurgery, 2024)
BACKGROUND: Gender disparities remain a significant issue, particularly impacting African women in the field of neurosurgery. - METHODS: Databases, articles, and perspectives were reviewed to identify challenges faced by African Women in Neurosurgery (AWIN), and explore solutions for recruit ment, retention, and career advancement of AWIN. - RESULTS: In 1982, Africa saw its first female neurosur geon, with the first female president of the World Federa tion of Neurosurgical Societies appointed 4 null decades later. Presently, the continent hosts 245 female neurosur geons, with North Africa comprising the majority at 76.3%, with Algeria notably contributing 72.2% of this total. Southern Africa contributes 7.8%, while West Africa, East Africa, and Central Africa contribute 6.5%, 6.1%, and 3.3%, respectively. Thirteen countries lack neurosurgeons entirely and 30 out of the 54 African nations face shortages of female neurosurgeons, with distributions as follows: North Africa (1-country), Southern Africa (6-countries), West Africa (8-countries), East Africa (9-countries), and Central Africa (6-countries). Our analysis mapped the dis tribution of 245 AWIN across the African regions and examined the professional trajectories and achievements of 17 pioneering AWIN. Additionally, we compiled registries for: 1) 76 neurosurgical training programs across 26 African countries, 2) organizations tackling gender disparities in neurosurgery, and 3) recommendations to promote AWIN across governmental, community, and academic spheres. - CONCLUSIONS: To boost AWIN representation in neurosurgery, concerted and comprehensive efforts are vital. Collaboration among medical schools, training programs, and governments is key to fostering diversity and inclusivity in African neurosurgical settings.
Research Article
Keywords: Africa; African women; Global neurosurgery; Neurosurgery; WINS; Women in neurosurgery